Teachers’ Strategies in Supporting School Readiness and Transition to Primary School after Pandemic Era - Dhieni, Nurbiana; Fridani, Lara; Wulan, Sri (JPUD - Jurnal Pendidikan Usia Dini, 2024)
According to some early childhood education experts, a child is ready for school if they have the specific information and abilities they need to do so. They define readiness in this sense as a state that must be achieved before studying at school. Previous research has linked sustained academic performance across life to preparation for school. In this study, the researchers examined the strategies used by kindergarten teachers to support children’s school readiness and transition to elementary school after the pandemic. Specifically, this research aims to find out the learning strategies implemented by kindergarten teachers when children return to school. Focus Group Discussions (FGD) for nineteen kindergarten teachers were used by researchers to collect narrative data, which was then studied using thematic analysis. Based on the results of qualitative data, researchers obtained information about various strategies implemented by teachers and the challenges they faced when accompanying children to learn. It is expected that the results of this research will provide enlightenment for early childhood teachers in general about the various strategies that need to be implemented to motivate children to learn so that they are ready for school and have a successful transition to elementary school. Keywords: early childhood, kindergarten teachers‘ strategy, school readiness, transition to elementary school References: Beaton, W., & McDonell, L. (2013). The transition into kindergarten: A community approach to integrating a child’s fragmented world – A discussion paper examining issues and implications of early childhood transitions to kindergarten. Nanaimo, BC: Tillicum Lelum Aboriginal Friendship Centre and Vancouver Island University. Cushon , J.A; Vu , Lan T; Janzen, T.B.L; & Muhajarine, N. (2011) Neighborhood Poverty Impacts Children’s Physical Health and Well-Being Over Time: Evidence From the Early Development Instrument, Early Education and Development, 22:2, 183-205, DOI: 10.1080/10409280902915861 Creswell J. W. (2013). Qualitative inquiry and research design: Choosing among five approaches. Thousand Oaks, CA: Sage. Dockett, S., Perry, & Kearney (2011). Facilitating children’s transition to school from families with complex support needs. Albury: Research Institute for Professional Practice, Learning and Education, Charles Sturt University. Fridani, L. (2014). School Readiness and Transition to Primary School: A Study of Teachers, Parents, and Educational Policy Makers’ Perspectives and Practices in the Capital City of Indonesia. Doctoral dissertation. Monash University, Australia. Halle, T. G., Hair, E. C., Wandner, L. D., & Chien, N. C. (2012). Pro- files of school readiness among four-year-old Head Start children. Early Childhood Research Quarterly, 27(4), 613–626. https://doi. org/10.1016/j.ecresq.2012.04.001. Harradine C. & Clifford R.M. (1996) When are Children Ready for Kindergarten? Views of Families, Kindergarten Teachers and Child Care Providers, paper presented at the Annual Meeting of the American Educational Research Association, New York, April. Hustedt, J. T., Buell, M. J., Hallam, R. A., & Pinder, W. M. (2017). While kindergarten has changed, some beliefs stay the same: kin- dergarten teachers’ beliefs about readiness. Journal of Research in Childhood Education, 32(1), 52–66. https://doi.org/10.1080/ 02568543.2017.1393031 Jensen, J. L., Goldstein, J., & Brunetti, B. A. (2021). Kindergarten readiness assessments help identify skill gaps .WestEd. Johnson, L. J., Gallagher, R. J., Cook, M., & Wong, P. (1995). Critical skills for kindergarten: Perceptions from kindergarten teachers. Journal of Early Intervention, 2, 315–349. Jiang, Y., & Monk, H. (2015). Young Chinese-Australian children’s use of technology at home: Parents and grandparents’s views. Asia Pacific Journal of Research in Early Childhood Education, 10 (1), 87-106. Laura, E.L., & Munsch,J. (2014). Child Development : An active Learning Approach. Sage Publications, Inc. Ma, Xin & Shen, Jianping & Krenn, Huilan. (2013). The relationship between parental involvement and adequate yearly progress among urban, suburban, and rural schools. School Effectiveness and School Improvement. 25. 629-650. 10.1080/09243453.2013.862281. McCain, M. N., Mustard, J. F., & McCuaig, K. (2011). Early years study 3: Making decisions taking action. Toronto,on: Margaret & Wallace McCain Family Foundation. Patton, M. Q. (2002). Two decades of developments in qualitative inquiry: A personal, experiential perspective. Qualitative social work, 1(3), 261-283 Petriwskyj, A.,Thorpe, K., & Tayler, C. (2005). Trends in construction of transition to school in three western regions, 1990-2004. International Journal of Early Years Education ,12, (2), 39-49. Puccioni, J. (2015) Parents’ Conceptions of School Readiness, Transition Practices, and Children’s Academic Achievement Trajectories, The Journal of Educational Research, 108:2, 130-147, DOI: 10.1080/00220671.2013.850399 Radesky, Jenny & Schumacher, Jayna & Zuckerman, Barry. (2015). Mobile and Interactive Media Use by Young Children: The Good, the Bad, and the Unknown. Pediatrics. 135. 1-3. 10.1542/peds.2014-2251. Reynolds, A. J. (2019). The power of P-3 school reform. Phi Delta Kappan, 100(6), 27-33. https://doi.org/10.1177/0031721719834025 Rosier, K. & Mc Donald,M. (2011). Promoting positive education and care transitions for children. The Australian Institute of Families Studies (13). Sayers,M., Moore,T., Brinkman, S., & Goldfled, S. (2012). The impact of reschool on children’s developemental oucomes and transition to school in Australia. Manuscript submitted for publication. Scott-Little, C., Kagan, S. L., & Frelow, V. (2006). Conceptualiza-tions of readiness and the content of early learning standards: The intersection of policy and research? Early Childhood Research Quar-terly, 21, 153–173. Venter, N.V., Joubert, J., & Chetty, R. (2014). Characteristics of a School, Community and Family Partnership to Increase Parental Involvement in Learning at Rural Multigrade Schools. Mediterranean journal of social sciences, 5, 1225. Vogler, P., Crivello, G. (2008). Early childhood transitions research: a review of concepts, theory, and practice. The Hague: Bernard van Leer Foundation. Xin Ma, Jianping Shen & Huilan Y. Krenn (2014) The relationship between parental involvement and adequate yearly progress among urban, suburban, and rural schools, School Effectiveness and School Improvement, 25:4, 629-650, DOI: 10.1080/09243453.2013.862281 Wesley, P. W., & Buysse, V. (2003). Making meaning of school readi- ness in schools and communities. Early Childhood Research Quarterly, 18(3), 351–375. https://doi.org/10.1016/s0885- 2006(03)00044-9. Williams, G. P., Lerner, M. A., Sells, J., Alderman, S. L., Hashi- kawa, A., Mendelsohn, A., McFadden, T., Navsaria, D., Pea- cock, G., Scholer, S., Takagishi, J., Vanderbilt, D., Pinto, C. D. L., Attisha, E., Beers, N., Gibson, E., Gorski, P., Kjolhede, C., O’Leary, S. C., & Weiss-Harrison, A. (2019, August 1). School Readiness. American Academy of Pediatrics. Zubrick, Taylor, & Christensen. (2015). Patterns and predictors of language and literacy abilities 4-10 years in the longitudinal study of Australian children.